Arterial Ischemic Stroke As a Complication to Disseminated Infection with Fusobacterium necrophorum - Ratnasingham, Yamuna; Kristensen, Lena Hagelskjaer; Gammelgaard, Lise; Balslev, Thomas (Neuropediatrics, 2014)
Lemierre syndrome (LS) is a rare complication of oropharyngeal and odontogenic infections in otherwise healthy young individuals. It is characterized by septic internal jugular vein thrombophlebitis and disseminated metastatic abscesses. Cerebral arterial ischemic stroke is rarely seen in LS. The authors present a 14-year-old, previously healthy girl, who developed cerebral arterial infarction following acute tonsillitis and abscess formations due to Fusobacterium necrophorum.
Keywords: arterial ischemic stroke; Fusobacterium necrophorum; Lemierre syndrome; inflammatory markers